(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Christian Unity and Solidarity - The Fruit of the Holy Spirit's work, but also the Foundation of the Democratic Society The Holy Spirit that animates our sincere prayer for Christian unity. For us it is a certainty that Christian unity has its origin and model into the life and nature of the three divine Persons. As urge prayers for unity, we have prayer in Gethsemane, Jesus, the only explicit prayer to God for Christian unity. In this prayer, although the name of the Holy Spirit is not spoken, it is present in every moment of this fervent prayers.